Inequality after the 20th century papers from the sixth ECINEQ meeting - Bishop, John A.; Rodri<U+0301>guez, Juan Gabriel (Bingley, U.K. : Emerald, 2016)
The essays in this series offer fresh theoretical and methodological insights into the key issues in the field of economic inequality. The content is comprised of highly topical subject matter with key researchers in the field contributing.
Reference groups and the poverty line: an axiomatic approach with an empirical illustration / Satya R. Chakravarty, Nachiketa Chattopadhyay, Joseph Deutsch, Zoya Nissanov, Jacques Silber -- The vulnerable are not (necessarily) the poor / Sanghamitra Bandyopadhyay -- Effects of reducing inequality in household education, health and access to credit on pro-poor growth: evidence from Cameroon / Boniface Ngah Epo, Francis Menjo Baye -- Labor market policies, informal labor markets and wage dispersion / Claudia Trentini -- The formal/informal employment earnings gap: evidence from Turkey / Aysit Tansel, Elif Oznur Acar -- The role of minimum wage and income transfer policies on the labour market: the case of Argentina / Fernando Groisman -- Performance and inequality in health: a comparison of child and maternal health across Asia / Benedicte Apouey, Jacques Silber -- Parental incarceration and social exclusion: long-term implications for the health and well-being of vulnerable children in the United States / Rosalyn Lee, Xiangming Fang, Feijun Luo -- Can a concern for status reconcile diverse social welfare programs? / Oded Stark, Marcin Jakubek -- How individuals' perceptions of inequality may affect their perceptions of corruption: a challenge to new democracies / Matthew Loveless -- Tax evasion and underground inequality: a parametric analysis / Roberto Fantozzi -- Macroeconomic determinants of inequality of opportunity in the United States: 1970-2009 / Gustavo A. Marrero, Juan Gabriel Rodri<U+0301>guez -- Occupational choice and earnings mobility in the work-life empirical evidence from Europe and the United States / Veronika V. Eberharter -- Relative income distribution in six European countries / Ilaria Petrarca, Roberto Ricciuti.
Includes bibliographical references.
Print version record
Keywords: Social Science Poverty & Homelessness; Welfare economics; Equality